2009
DOI: 10.1093/brain/awp053
|View full text |Cite
|
Sign up to set email alerts
|

Gait freezing in Parkinson's disease and the stride length sequence effect interaction

Abstract: Freezing of gait (FOG) has been identified as one of the main contributors to gait disturbances in Parkinson's disease. While the pathophysiology remains enigmatic, several factors such as step length and the sequence effect (step to step reduction in amplitude) may lead to the occurrence of FOG. It was hypothesized that by reducing step length, FOG episodes would present more frequently if a significant sequence effect (measured as a regression slope) was co-existent in the subject. Twenty-six participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
215
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(245 citation statements)
references
References 24 publications
22
215
5
2
Order By: Relevance
“…For example, freezing behaviour is associated with a progressive reduction in step size (the sequence effect) set on top of a low baseline step length (hypokinesia) (Nieuwboer et al, 2001;Iansek et al, 2006;Chee et al, 2009). We have shown that doorways provoke decreases in velocity and stride length.…”
Section: Freeze Behaviour In Doorwaysmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, freezing behaviour is associated with a progressive reduction in step size (the sequence effect) set on top of a low baseline step length (hypokinesia) (Nieuwboer et al, 2001;Iansek et al, 2006;Chee et al, 2009). We have shown that doorways provoke decreases in velocity and stride length.…”
Section: Freeze Behaviour In Doorwaysmentioning
confidence: 83%
“…A parsimonious explanation for these disparate phenomena is that they result from involuntarily exaggerated responses to action-relevant visual information during walking in PD. As a result, visual information may promote or constrain walking depending on what possibilities it suggests for action: lines on the ground become readily stepped over but road-crossings produce an exaggerated slowing down which may in turn cause freezing episodes (Chee et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Most studies focused their analyses on steady-state walking, reporting that leg EMG activity is reduced, and that the results are basically consistent with those observed in arm and finger movements (Evarts et al 1981;Wing 1988;Cioni et al 1997;Chee et al 2009). In addition, it has been reported that the impairment of gait initiation is associated with the visuospatial cognitive environment (Azulay et al 1999;Cummings and Steven 1992;Naismith et al 2010).…”
Section: Introductionmentioning
confidence: 65%
“…l congelamiento o "freezing" en la marcha (FM) es un fenómeno caracterizado por episodios transitorios de trastorno motor, mantenido algunos segundos, comúnmente observado en la enfermedad de Parkinson (EP), afectando a más de un tercio de los individuos [1][2][3] , siendo descrito por los pacientes como la sensación de tener los pies "pegados al suelo" 4 . Puede ser desencadenado al intentar iniciar y/o continuar la marcha, ante restricciones ambientales que exijan cambios en la velocidad, patrón o sentido del paso con o sin presencia de obstáculos o al caminar en espacios cerrados.…”
unclassified